Soluble SIRP-Alpha Promotes Murine Acute Lung Injury Through Suppressing Macrophage Phagocytosis - Shen, Qinjun; Zhao, Li; Pan, Linyue; Li, Dandan; Chen, Gang; Chen, Zhihong; Jiang, Zhilong (Frontiers in Immunology, 2022)
Soluble signal regulatory protein-alpha (SIRP-alpha) is elevated in bronchoalveolar lavage (BAL) of mice with lipopolysaccharides (LPS)-induced acute lung injury (ALI). To define the role of soluble SIRP-alpha in the pathogenesis of ALI, we established murine ALI in wild-type (WT) and SIRP-alpha knock-out (KO) mice by intratracheal administration of LPS. The results indicated that lack of SIRP-alpha significantly reduced the pathogenesis of ALI, in association with attenuated lung inflammation, infiltration of neutrophils and expression of pro-inflammatory cytokines in mice. In addition, lack of SIRP-alpha reduced the expression of pro-inflammatory cytokines in LPS-treated bone marrow-derived macrophages (BMDMs) from KO mice, accompanied with improved macrophage phagocytosis. Blockade of soluble SIRP-alpha activity in ALI BAL by anti-SIRP-alpha antibody (aSIRP) effectively reduced the expression of TNF-alpha and IL-6 mRNA transcripts and proteins, improved macrophage phagocytosis in vitro. In addition, lack of SIRP-alpha reduced activation of Src homology 2 domain-containing protein tyrosine phosphatase 1 (SHP-1) and improved activation of signal transducer and activator of transcription-3 (STAT3) and STAT6. Suppression of SHP-1 activity by tyrosine phosphatase inhibitor 1 (TPI-1) increased activation of STAT3 and STAT6, and improved macrophage phagocytosis, that was effectively reversed by STAT3 and STAT6 inhibitors. Thereby, SIRP-alpha suppressed macrophage phagocytosis through activation of SHP-1, subsequently inhibiting downstream STAT3 and STAT6 signaling. Lack of SIRP-alpha attenuated murine ALI possibly through increasing phagocytosis, and improving STAT3 and STAT6 signaling in macrophages. SIRP-alpha would be promising biomarker and molecular target in the treatment of murine ALI and patients with acute respiratory distress syndrome (ARDS).